Aggressive angiomyxoma of the vagina: a case report - Lourenço,Cátia (2013)
Aggressive angiomyxoma is a rare, slow-growing soft tissue tumor that usually arises in the pelvis and perineal regions of women in reproductive age, with a marked tendency to local recurrence. Because of its rarity, it is often initially misdiagnosed. Surgical resection is the main treatment modality of aggressive angiomyxoma. We describe a case of a vaginal aggressive angiomyxoma in a 47-year-old woman in which the diagnosis was only made after histological examination. The etiology, presentation, diagnosis and management of this rare tumor are outlined. Angiomyxoma of vulva and vagina refers to a rare disease. Pre-operative diagnosis is difficult due to rarity and absence of diagnostic features, but it should be considered in every mass in genital, perianal and pelvic region in a woman in the reproductive age. Thus, these cases should have complete radiological workup before excision, as pre-diagnosis can change the treatment modality and patient prognosis'.